2021
DOI: 10.3126/researcher.v5i1.41384
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Low Performing Students Perception towards Mathematics: A Case of Secondary Level Community School Students of Nepal

Abstract: The students' perception of mathematics is equally important for the parents as well as the teachers to deal with them effectively. Therefore, this study is concerned with the secondary level low-performing students' perception of mathematics and its effects on their achievements. The study is based on the mixed-method survey research design consisting of 312 grade IX and X students, 119 male and 193 female students from the 10 community schools of Province No. 1, Nepal. A Likert-type survey questionnaire, 'Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The abstract nature of calculus can result in a negative attitude toward mathematics and science at secondary and university levels. It can also lead to persistent poor performance in mathematics and a low rate of students enrolled in mathematics options (De Vera et al, 2022;Kunwar, 2021).…”
Section: Research Problemmentioning
confidence: 99%
“…The abstract nature of calculus can result in a negative attitude toward mathematics and science at secondary and university levels. It can also lead to persistent poor performance in mathematics and a low rate of students enrolled in mathematics options (De Vera et al, 2022;Kunwar, 2021).…”
Section: Research Problemmentioning
confidence: 99%
“…Problems in learning mathematics may be caused by different factors related to the curriculum, teachers, and learners. Learners' negative perceptions toward mathematics due to a sense of fear and failure can generate problems in learning mathematics (Kunwar, 2021). Similarly, the lack of effective instructional practices as well as student support considering their individual needs can also create mathematics learning problems (Causarano, 2015).…”
Section: Problems Of Learning Mathematicsmentioning
confidence: 99%
“…Similarly, the lack of effective instructional practices as well as student support considering their individual needs can also create mathematics learning problems (Causarano, 2015). Also, the improper organization of the subject matter or curriculum can create differences in each of the learners (Kunwar, 2021). The problem regarding the teachers' factor is related to the teachers' knowledge and experience, and skills in utilizing proper methods, tools, and techniques in pedagogical practices.…”
Section: Problems Of Learning Mathematicsmentioning
confidence: 99%
“…It was found that perception of mathematics has no influence or effect on their academic performance. Kunwar (2021) in his paper included the parents and teachers in his secondary low-level performing students' perception of Mathematics. The result revealed negative with respect to perception and performance to learn Mathematics but they knew the value of learning Mathematics.…”
Section: Aesthetic Value and Math Performance Upon Using The Teacher-...mentioning
confidence: 99%